Model Hermeneutika Friedrich Schleiermacher dan Relevasinya dengan Ilmu Tafsir Al-Qur’an - Abdul Rohman (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2023)
This article discusses the hermeneutics of F. Schleiermacher and its relevance to the science of interpretation of the Koran. The purpose of writing this article is to find out how explains Schleiermacher’s theory of hermeneutics with two theories namely grammatical and psychological hermeneutics and its relevances to the science of interpretation of the Koran. Writing this research using qualitative methods which is based on library research and is based on direct sources by Schleiermacher. The results obtained are that according to Schleiermacher hermeneutics should be applied to all disciplines and to get an objective meaning have to go two method its namely with the theory of grammatical hermeneutics which focuses on the study of early language used at the appear of a text and psychological hermeneutics theory which is based on the author’s psychological knowledge. The two method must be done gradually, so that method the meaning of a text can be obtained as objectively as possible. In the Islamic scientific tradition the two method Scholars have been doing this for a long time, used to reveal the meaning of the verses of the Koran, so the relevances is very clear.